Fabrication and scintillation properties of a flexible optical-guiding crystal scintillator. (17th February 2023) - Yajima, Ryuga; Kamada, Kei; Murakami, Rikito; Kutsuzawa, Naoko; Sasaki, Rei; Yoshino, Masao; Horiai, Takahiko; Kim, Kyoung Jin; Kochurikhin, Vladimir V.; Yamaji, Akihiro; Kurosawa, Shunsuke; Yokota, Yuui; et al.
Abstract: Scintillation properties of a flexible optical-guiding crystal scintillator with a thallium-doped CsI (Tl:CsI) crystal and borosilicate glass as the core and cladding, respectively, are reported. The as-fabricated optical-guiding crystal scintillator exhibits a light yield of 31, 000 photons MeV −1 under 662 keV γ -ray irradiation. The recrystallized sample is transparent and provides a higher light yield of 54, 000 photons MeV –1, which is comparable to that of single-crystal Tl:CsI. The decay times are 400 ns (28%) and 1, 350 ns (72%). This material can serve as a scintillator fiber with high sensitivity to γ - and X-rays, high light yield, and energy discrimination.